When leaders “stoop”: dual-path mechanisms and social connection reconstruction of humble leader behavior to dispel occupational stigma consciousness - Zhang, Kaituo; Ma, Shuo; Zhang, Yaqian (Frontiers in Psychology, 2025)
This study aims to explore the mechanism and path of influence of humble leader behavior on the occupational stigma consciousness of non-decent workers. Based on social exclusion theory and resource conservation theory, we constructed a dual-path model of “social isolation-professional identification.” We introduced leadership relational identification as a moderator variable to systematically analyze how humble leaders can indirectly reduce occupational stigma consciousness by reducing social isolation and enhancing professional identification, and then promote proactive behavior and job accomplishment. Through open coding and categorizing the inter-view texts of 20 nurses using grounded theory, the study refined the relationships of the core variables to form a qualitative analysis framework of the pathways of occupational stigma consciousness, and tested the hypotheses through structural equation modeling and hierarchical regression analysis using a multi-temporal tracking design with a sample of 731 nurses in eastern China. The results of the study indicate the following: Firstly, humble leader behavior exerts a significant negative influence on occupational stigma consciousness, while concurrently promoting proactive behavior and job accomplishment. Secondly, social isolation and professional identification partially mediate the relationship between humble leader behavior and occupational stigma consciousness. Thirdly, leadership relational identification positively moderates the effects of humble leader behavior on social isolation and professional identification. From a theoretical standpoint, this study proposes a dual-path intervention model of occupational stigma consciousness, which deepens the mechanism of leadership and the theory of stigma management. From a practical standpoint, it provides empirical evidence for organizations to optimize the psychological resources of non-decent workers and build inclusive environments through humble leadership behaviors. The findings of the study carry significant ramifications for the enhancement of the experience of non-decent workers and the augmentation of the sustainable performance of organizations.